BEYOND GLYCEMIC CONTROL: ASSESSING ADHERENCE AND BARRIERS TO ANNUAL SCREENING RECOMMENDATIONS FOR DIABETIC COMPLICATIONS IN HOSPITALIZED PATIENTS AT A TERTIARY CARE HOSPITAL IN PAKISTAN. - Muhammad Usman Sharif; Muhammad Hamza; Abrar Ali Shah; Syeda Amal Fatima; Hamza Ali Khan; Hina Jamshed; Saad Qadeer; Muqadas Munir; Naeem Haider Shah; Ahmad Munawar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Diabetes mellitus (DM) poses a rapidly growing public health challenge in Pakistan, with a high burden of preventable microvascular and macrovascular complications. International guidelines recommend annual screening for complications such as retinopathy, nephropathy, neuropathy, dyslipidemia, and cardiovascular risk, yet adherence to these recommendations remains poorly studied in hospitalized diabetic populations. This study aimed to assess adherence to guideline-recommended annual complication screening and to identify barriers and associated factors among hospitalized diabetic patients in a tertiary care hospital in Pakistan. Methods: A hospital-based, cross-sectional study was conducted in the Department of Medicine at Ayub Teaching Hospital, Abbottabad, from September 2024 to January 2025. Four hundred adult patients with known diabetes mellitus admitted to medical wards were enrolled using consecutive sampling. Data on demographics, clinical history, recent HbA1c levels, and documentation of recommended annual screening tests were collected through structured questionnaires and record review. Adherence was categorized as full, partial, or none. Associations between adherence and patient characteristics were analyzed using Chi-square tests, t-tests/ANOVA, and logistic regression to identify independent predictors of non-adherence. Results: The mean age of participants was 56.8 ± 11.9 years, with 54.5% males and 91.2% having type 2 DM. The mean duration of diabetes was 9.6 ± 6.1 years, and 69.2% had poor glycemic control (HbA1c > 7%). Only 91 patients (22.8%) were fully adherent, 185 (46.2%) were partially adherent, and 124 (31.0%) were non-adherent to all annual screenings. Blood pressure monitoring (92.3%) and lipid profiling (64.7%) had the highest adherence rates, whereas retinal examination (24.5%) and comprehensive foot examination (19.8%) showed the lowest. Younger age (<60 years), shorter duration of diabetes (<10 years), and good glycemic control (HbA1c ≤ 7%) were significantly associated with higher adherence (p < 0.05). Multivariate analysis identified older age (AOR 1.72, 95% CI 1.11–2.66), longer disease duration (AOR 1.48, 95% CI 1.01–2.19), and poor glycemic control (AOR 2.36, 95% CI 1.48–3.77) as independent predictors of non-adherence. Financial constraints (40.1%), lack of awareness (30.1%), and limited access to specialist services (18.1%) were the most frequently cited barriers. Conclusion: Adherence to annual complication screening among hospitalized diabetic patients was suboptimal, with fewer than one-quarter achieving full adherence. This highlights a critical gap in preventive diabetes care. Addressing financial barriers, improving patient education, and integrating standardized screening protocols into inpatient care could enhance adherence and reduce the long-term burden of diabetes-related complications in Pakistan.